Nothing Special: Great Fact of Faith and Its Naturalistic Explanation - Ruczaj, Stanisław (Roczniki Filozoficzne, 2023)
In his book Między ukryciem a jawnością [Between Hiddenness and Openness] (2023), Professor Jacek Wojtysiak argues that on the assumption of atheistic naturalism, no convincing explanation can be given for the ‘great fact of faith,’ that is, the phenomenon of the historical persistence and universality of the belief in the existence of God. The purpose of this paper is to challenge this thesis. Drawing on selected theories from the field of the Cognitive Science of Religion, I sketch a naturalistic explanation of how religious belief arises.